Unravelling organizational consequences of PSI reform: An in-depth study of the organizational impact of the reuse of public sector data - Marcel Veenswijk; Henk Koerten; Jaap Poot (The Research Institute of the Finnish Economy (ETLA), 2012)
The success of Google Maps suggests that free access to public sector information (PSI) contributes to a prosperous economy. While there has been considerable attention for legal and economical considerations concerning the implications of policies on public sector information (PSI), also labeled as open data (OD), organizational consequences regarding the nature and shape of the public sector are hardly anticipated. We focus on organizational settings by comparing policies and outcomes of PSI reuse in EU member states and are looking into distinct market sectors within the European realm by making analyses of both a Dutch national case and a cross-national case. In many discussions on PSI reuse, government is treated as a unitary phenomenon with a single voice. We found considerable differences among EU member states concerning the implementation of PSI policies and that there are indications that they are connected to the nature of the public sector in a specific state. Furthermore, we discovered that where specific actions stimulate the creation of arenas of opportunity with both public and private parties gathered around a specific information theme, new innovative arrangements emerge. Therefore we suggest that policies on PSI reuse to stimulate economic prosperity should be aimed at creating arenas of public and private organizations gathered around specific PSI themes. This will stimulate PSB organizations to engage actively in arrangements with multiple private organizations to develop new forms of reuse. When national government develops policies aimed simply at disclosing PSI without paying attention to the development of PSI reuse arenas, it runs the risk of unleashing narratives of control within the public sector, preventing them from releasing the innovative potential that PSI reuse intrinsically has.
Keywords: 330; Öffentlicher Sektor; Informationsdienstleistung; Informationsmanagement; Neues Steuerungsmodell; E-Government; EU-Staaten; Niederlande